Infectivity and molecular epidemiology of Peste des Petits ruminants virus in slaughtered goats at the local meat market of Mymensingh division, Bangladesh. (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The purpose of this study was to characterize the circulating Peste des Petits Ruminants virus (PPRV) from slaughtered goats and conduct a phylogenetic analysis of the N gene of PPRV. Materials and Methods: A total of 196 slaughtered goats were investigated at the marketplaces of Mymensingh division from January 2019 to March 2021. Lungs, spleen, and mesenteric lymph nodes were collected for histology and molecular study. In-house developed Reverse-Transcriptase-Polymerase Chain Reaction (RT-PCR) protocols were carried out using designed primer sets (PPRV NF-gctctgtgattgcggctgagc and PPRV NR-cctggtcctccagaatcttggcc). The CLC sequence viewer was used for phylogenetic analysis. Results: Grossly pneumonic lungs, shrinkage spleen, and enlarged mesenteric lymph nodes with hemorrhages were recorded. Both intracytoplasmic and intranuclear inclusion bodies were seen in lymphocytes of the mesenteric lymph node, spleen, and lungs. PPRV was detected in 37 goats (18.9%) by RT-PCR test. The 402-bp amplicon was generated in PPRV-positive cases. The phylogenetic analysis showed that the studied PPRV isolates of the Mymensingh division belonged to lineage IV. Conclusion: The prevalence of PPR was 18.9% in slaughtered goats at marketplaces in the Mymensingh division. Slaughterhouses may be a source of PPRV, and it can be horizontally transmitted from the meat market to the farm. Restricting sick animal movement within the country, mass PPR vaccination campaigns, increased awareness, and improved biosecurity in the meat market may lessen the incidence of PPR in goats.J. Adv. Vet. Anim. Res., 11(3): 655–663, September 2024http://doi.org/10.5455/javar.2024.k815